ELEMENTAL AND SR-ND-PB ISOTOPIC GEOCHEMISTRY OF THE WENDUERMIAO AND BAYANAOBAO-JIAOQIER OPHIOLITES, INNER MONGOLIA: CONSTRAINTS FOR THE CHARACTERISTICS OF THE MANTLE DOMAIN OF EASTERN PALEO-ASIAN OCEAN - Huang J.X.; Zhao Z.D.; Hou Q.Y.; Chen Y.L.; Zhang H.F.; Zhang B.R.; DePaolo D.J. (My University, 2006)
There are three ophiolites sited in central Inner Mongolia, representing the sutures between North China craton and Siberia plate. Elemental and Sr-Nd-Pb isotopic geochemistry of the meta-basaltic rocks in Wenduermiao and Bayanaobao-Jiaoqier ophiolites were studied in this paper. The Wenduermiao alkli meta-basaltic rocks are enriched in light REE, showing the futures of within-ocean and intercongtinental rift basalt. This indicates possibly the early stage opening of a new ocean around 600Ma ago during the long-term evolution of Paleo-Asian Ocean. The Bayanaobao-Jiaoqier rocks collected from Suzuoqi are divided into two groups, the first group show ocean island basalt (OIB) features, with the light REE enrichment; the second have ocean island arc basalt (OIA) signature, displaying negative anomalies of Nb and Ta. These OIB and OIA basalts occurred in Bayanaobao-Jiaoqier ophiolite suggest the existence oceanic subduction related process within the Paleo-Asian Ocean around 400Ma ago. Systemic comparisons of elemental and isotopic geochemistry were made between the OIB in this study and that from the Tethyan Ocean in southwestern China. The results indicate that they have different features, the OIB in Paleo-Asian Ocean have the high U/Pb (HU) and north Atlantic and Pacific Ocean MORB province features, while the Tethys have the Indian Ocean MORB province feature. These results suggest that the mantle domains of Paleo-Asian Ocean and Tethys are two independent systems, each with different isotopic geochemical features.
Keywords: GEOCHEMISTRY; INNER MONGOLIA; ISLAND ARC; MANTLE DOMAIN; OCEAN ISLAND BASALT; PALEO-ASIAN OCEAN